(untitled) (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2022)
This study examines the impact of implementing multiple representation method in responding to the challenge of learning science specifically in relation to enhancing students’ reasoning skill. Pre-experimental method was applied to obtain research data from participants consisted of 8th grader students at a private junior high school in Bandung, Indonesia. The effect on reasoning skill was studied from students’ arguments in answering question related to respiratory system. The arguments were then analyzed by the completeness of argument component, level of argument, and quality of argument referring to Toulmin’s argumentation pattern (TAP). The findings show that students experienced significant improvement in reasoning skill expressed in their arguments. The improvement was evident in the higher argument level and better argument quality achieved by students after the implementation of multiple representation method. In relation to quality of argument, the overall quality of argument shifted from the domination of weak arguments to the domination of strong arguments. Additionally, the use of multiple representation in learning assists students to be able to use various forms of information such as graphics, visual images, tables, scientific formula, and written expression in explaining concepts.